2017
DOI: 10.1051/0004-6361/201730553
|View full text |Cite
|
Sign up to set email alerts
|

SMC X-3: the closest ultraluminous X-ray source powered by a neutron star with non-dipole magnetic field

Abstract: Aims. Magnetic field of accreting neutron stars determines their overall behavior including the maximum possible luminosity. Some models require an above-average magnetic field strength ( 10 13 G) in order to explain super-Eddington mass accretion rate in the recently discovered class of pulsating ultraluminous X-ray sources (ULX). The peak luminosity of SMC X-3 during its major outburst in 2016-2017 reached ∼ 2.5 × 10 39 erg s −1 comparable to that in ULXs thus making this source the nearest ULX-pulsar. Deter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
87
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(104 citation statements)
references
References 50 publications
15
87
0
Order By: Relevance
“…In this case, we could have a situation where the cyclotron line is produced close to the NS in a stronger magnetic field affected by the multipoles, while the disk only feels the weaker dipole field away from the NS, allowing the matter to come closer to the NS. We note that Tsygankov et al (2017) invoked the same argument to explain the small magnetosphere size in ultra-luminous X-ray pulsar SMC X-3.…”
Section: Inner Disk Radius In Gro J1744−28mentioning
confidence: 52%
“…In this case, we could have a situation where the cyclotron line is produced close to the NS in a stronger magnetic field affected by the multipoles, while the disk only feels the weaker dipole field away from the NS, allowing the matter to come closer to the NS. We note that Tsygankov et al (2017) invoked the same argument to explain the small magnetosphere size in ultra-luminous X-ray pulsar SMC X-3.…”
Section: Inner Disk Radius In Gro J1744−28mentioning
confidence: 52%
“…From 2016 August to 2017 March, SMC X-3 underwent a superEddington outburst with a peak luminosity of ∼ 10 39 erg/s, making it as the most luminous giant outburst reported in BeXRBs (Weng et al 2016(Weng et al , 2017Townsend et al 2017;Tsygankov et al 2017). Investigating the follow-up Swift monitoring observations, we found that the pulse profile exhibited a doublepeak profile at the high luminosity state and then merging into the single peak at the low luminosity (Weng et al 2017, hereafter Paper I).…”
Section: Introductionmentioning
confidence: 73%
“…SMC X-3 was visited by Nustar at a high luminosity state during the 2016-2017 giant outburst rise (on 2016 August 13), one XMM-Newton (2016 October 14) and the second Nustar observations (2016 November 12) were subsequently carried out at the intermediate luminosity level during the decay of outburst (Table 1). The phase-averaged spectrum of XMM-Newton has been reported in Paper I, and the Nustar observations have been partially analyzed in Tsygankov et al (2017). Since both XMM-Newton and Nustar have the large effective areas, high time resolution and moderate energy resolution, we present a detailed pulse phaseresolved analysis on these high quality data to explore the nature of accretion flows in this extreme outburst.…”
Section: Introductionmentioning
confidence: 99%
“…As the accretion rate increases, radiation pressure becomes important. For pulsar-scale magnetic fields, µ ∼ 10 30 G cm 3 , this happens at luminosities of a few times L Edd , which are quite reachable, for instance, in Be/X-ray binaries during strong outbursts like the recent super-Eddington outburst of SMC X-3 (Townsend et al 2017;Tsygankov et al 2017). As we have shown in CAP (see eq.…”
Section: Magnetospheric Radius For Different Accretion Regimesmentioning
confidence: 99%